Statement by the Managing Director on the Interim Work Program of the Executive Board. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This interim work program statement reflects the imperative of accelerating the process of reform that has been underway in the Fund for some time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Liberia